A STUDY FOR THE CAUSES OF VARIATION ORDERS IN DIFFERENT SECTORS OF CONSTRUCTION PROJECTS IN ERBIL GOVERNORATE FROM THE POINT OF VIEW OF THE INVOLVED PARTIES - Jihad Mohammed, Aksana (Journal of Engineering and Sustainable Development, 2016)
A Variation order is a common phenomenon in any project. There are many causes that may lead to variation order in a construction project. This paper aims to investigate and identify the most significant causes of variation orders in different sectors of construction in Erbil Governorate, and their effects on the projects in order to manage them and find the solutions that can eliminate them by putting some control measures. This research was conducted by a questionnaire survey to elicit 30 causes of variation orders from the point of view of owners, consultant engineers, and contractors. A questionnaire was submitted to a sample of 140 persons who specialized in the construction sector in the Erbil Governorate. Out of 140 questionnaires, 120 were returned forming 18 owners, 62 consultant engineers, and 40 contractors. Then the questionnaire was analyzed statistically. Also, a case study was adopted for 30 projects of different construction sectors that were constructed from 2010-to 2013 to calculate the percentage of cost and time overrun due to variation orders. Also, a comparison study had made among the results obtained from this study and some countries for the major causes of variation orders in construction projects. The results of the questionnaire indicate that the Owner and consultant engineer is the most responsible parties causing changes. The most important causes of variation orders in construction projects in Erbil Governorate are changes in the bill of quantities, changes of plans, or schedule by the Owner...